Mandi Kembang, Fenomena Sosial Mendapatkan Jodoh Bagi Perempuan di Kalimantan Selatan - Nimah Nimah; I.B Wirawan (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
In general, unmarried adult women who live in a married culture will receive pressure from their parents, friends, and the environment to get married. Subsequently, the belief in the myth of the flower bath ritual is developed in society, aiming to make a soul mate closer. Flower bath is a traditional ritual of the belief of the people in South Kalimantan, especially in Barabai, which is believed to be able to bring a soul mate. The soul mate who was invited by carrying out the flower bath has become a discourse that has been strongly constructed in the cultural roots and customs of the Barabai people. The victims, in this case, are girls; if the girl is of the age that is considered sufficient for marriage and does not have a partner, then the trusted way is to do the flower bath ritual. Demands for marriage to girls are related to several factors, including culture, social, and economy. This article uses qualitative research methods and phenomenological approach, The purpose of this study was to determine descriptively the phenomena of a flower bring soulmate The results show that the flower bath is inseparable from the cultural teachings of Hinduism that entered Kalimantan since the 4th century. In addition, community leaders presume that culture is cultural acculturation where Islam enters by Islamizing the culture.